2004
DOI: 10.1039/b308864m
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalyzed carbon–carbon bond activation

Abstract: This tutorial review deals with recent developments in the activation of C-C bonds in organic molecules that have been catalyzed by transition metal complexes. Many chemists have devised a variety of strategies for C-C bond activation and significant progress has been made in this field over the past few decades. However, there remain only a few examples of the catalytic activation of C-C bonds, in spite of the potential use in organic synthesis, and most of the previously published reviews have dwelt mainly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
309
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 949 publications
(312 citation statements)
references
References 51 publications
(70 reference statements)
0
309
0
3
Order By: Relevance
“…The use of Ph 3 PAuNTf 2 catalyst also shows somewhat similar results (entry 2). Next, various Lewis acids catalysts such as Cu(OTf) 2 , Zn(OTf) 2 , Yb(OTf) 3, In(OTf) 3 , Sc(OTf) 3 and Bi(OTf) 3 has been investigated (entries [3][4][5][6][7][8] . The best result was obtained with 5 mol% of Sc(OTf) 3 in MeOH that afforded 2a/3a in 87% yield with good regioselectivity (23:1) (entry 7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of Ph 3 PAuNTf 2 catalyst also shows somewhat similar results (entry 2). Next, various Lewis acids catalysts such as Cu(OTf) 2 , Zn(OTf) 2 , Yb(OTf) 3, In(OTf) 3 , Sc(OTf) 3 and Bi(OTf) 3 has been investigated (entries [3][4][5][6][7][8] . The best result was obtained with 5 mol% of Sc(OTf) 3 in MeOH that afforded 2a/3a in 87% yield with good regioselectivity (23:1) (entry 7).…”
Section: Methodsmentioning
confidence: 99%
“…Literature scrutiny revealed that significant progress has been made in the field of this research; however, this chemistry has been mainly limited to ringstrained molecules [5][6][7][8][9][10] and specially designed model compounds. 11,12 Herein, we report Sc(OTf) 3 catalysed C-C bond cleavage in ynones that leads to synthesis of ketones that from ynones would have poor atom economy of ketones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the activation of dihydrogen [1] and subsequently carbon-hydrogen bond activation have been achieved with a large selection of powerful methods, [2][3][4][5] the activation and cleavage of carbon-carbon (C À C) bonds has attracted much less attention. [4][5][6][7] Methodologically it is to be regarded as problematic. There are classical methods known for the selective cleavage of strong unactivated C À C bonds, such as the ozonolysis cycloaddition/cycloreversion sequence [8,9] or the metal-catalyzed olefin metathesis reaction.…”
mentioning
confidence: 99%
“…Eine wirklich universelle Methode gibt es bis heute jedoch nicht, woraus sich eine große Herausforderung für die organische Synthese ergibt. [3] Die bisher beschriebenen Strategien zur selektiven Aktivierung der C-C-Einfachbindung beruhen zumeist auf der Verwendung gespannter Ringe, [4] der Wirkung von Chelatbildnern [5] und der Bildung von Metallalkoholaten zur b-Alkyl-Eliminierung. [6] Zwei jüngste Beiträge von Kuninobu und Takai et al über die Rhenium(I)-katalysierte Bildung von C-CBindungen durch direkte C-H-Aktivierung zeigen nun eine gänzlich neue Reaktionsweise auf.…”
unclassified